ANALYSIS OF THE EFFECTIVENESS AND EFFICIENCY OF PERFORMACE-BASED BUDGET EXPENDITURE AT THE INDONESIAN FOOTWEAR INDUSTRY EMPOWERMENT CENTER FOR PERIOD 2020-2024 - Ira Safiratul Ulum; Akhmad Mulyadi (International Journal of Economic Integration and Regional Competitiveness, 2026)
Objective: This study aims to analyze the effectiveness and efficiency of performance-based budget spending at the Indonesian Footwear Industry Empowerment Center (BPIPI) during the 2020–2024 period. Method: The research uses a descriptive quantitative method with secondary data obtained from official institutional reports. Data analysis was conducted through the measurement of budget performance values using effectiveness and efficiency indicators. Results: The results show that BPIPI's budget performance has generally been implemented effectively and efficiently. The overall budget performance values were categorized as good and very good, reaching 86.55% in 2020, 99.78% in 2021, 97.53% in 2022, 98.60% in 2023, and 93.32% in 2024. Novelty: These findings indicate BPIPI's commitment to improving budget management and achieving organizational performance targets despite various internal and external challenges during the implementation period.